Perancangan Prototype Alat Penjemur Pakaian Otomatis Berbasis Mikrokontroler Atmega 328 - Hidayat, Taufik; Akbar, Muhammad; Mursalim, Mursalim (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Rain or bad weather has been a major problem for people who have clotheslines. Usually, clothes that are dried are often left out, so there is no time to pick up the clothesline when it rains or at night. To overcome this problem, an automatic clothesline control system is needed. By designing all the tools starting from the Light Dependent Resistor (LDR) Sensor as a light detector, water sensor as a rainwater detector, Stepper Motor as a driver, and Arduino Uno as a command maker. From the results of testing the tools that have been designed, the tool works every time the sensor reads the surrounding weather, such as when the sensor does not detect light, the Arduino will translate the surrounding conditions as dark, so that the Stepper motor will pull the clothesline inside. When the LDR sensor detects sunlight, the Arduino will translate the weather around the heat, automatically the clothesline will come out. Meanwhile, when the water sensor detects water droplets, it is translated by Arduino as rainy weather, then the Stepper motor will pull the clothespins in